1992
DOI: 10.1093/jn/122.1.191
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Pancreatic Exocrine Secretion in Ruminants: A Review , ,

Abstract: Mechanisms regulating ruminant pancreatic exocrine function differ in some respects from those in nonruminants. This may affect the post-ruminal digestion of certain dietary nutrients such as starch. Ruminants do not exhibit clearly defined cephalic and gastric phases of pancreatic regulation, a likely consequence of the continuous nature of digesta flow from the rumen. Local neural reflexes and secretin-mediated exocrine responses may be more important than stimulation by cholecystokinin. Additionally, the ru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
3

Year Published

1994
1994
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 49 publications
0
21
0
3
Order By: Relevance
“…In numerous studies it was shown that shortchain fatty acids, especially propionic and butyric acids, are the main factors responsible for pancreatic enzymes secretion in ruminants (Croom et al, 1992;Żebrowska et al, 2001). Thus, increased concentration of butyric and isoacids in rumen fluid in sheep supplemented with QUE diet (our unpublished data) could be also the reason of elevated activity of pancreatic lipase.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…In numerous studies it was shown that shortchain fatty acids, especially propionic and butyric acids, are the main factors responsible for pancreatic enzymes secretion in ruminants (Croom et al, 1992;Żebrowska et al, 2001). Thus, increased concentration of butyric and isoacids in rumen fluid in sheep supplemented with QUE diet (our unpublished data) could be also the reason of elevated activity of pancreatic lipase.…”
Section: Discussionmentioning
confidence: 58%
“…In contrast to monogastric animals, in ruminants the secretion of pancreatic juice and bile is permanent because of the constant flow of digesta to the duodenum, without separating period between feeding (Croom et al, 1992).…”
Section: Discussionmentioning
confidence: 97%
“…Further, pancreatic endocrine secretion is sensitive to CCK and secretin in ruminants (Croom et al, 1992). Secreted CCK from the fundus of the small intestine is known to stimulate pancreatic secretion through the afferent pathway of the vagus nerve (Li and Owyang, 1993; Eastwood et al, 1998).…”
Section: Resultsmentioning
confidence: 99%
“…Croom et al. () also reported that the nervous system plays a major role in the control of pancreatic exocrine secretion and stated that stimulation of the vagus nerve causes enhanced secretion of α ‐amylase. Because the vagus nerve interfaces with the parasympathetic nervous system, it seems logical that, as adrenaline or cortisol blocks this interface, α ‐amylase activity would be reduced.…”
Section: Discussionmentioning
confidence: 99%